Nafkah dalam Al-Qur’an: Urgensi Pemberian Nafkah oleh Suami kepada Istri dalam Menjalin Hubungan Rumah Tangga Berdasarkan Q.S An-Nisa(4): 34 - Mardiana, Abdilah Reza (Maliki Interdisciplinary Journal, 2024)
The emergence of various problems related to maintenance in household relationships has caused a lot of rifts in household relationships. This is partly due to the low knowledge of family law among the community. The purpose of this research is as a tool to find out the urgency of providing maintenance in establishing household relationships. The method used in conducting this research is through normative juridical research with a literature study method through secondary data searches. In addition, by using the maudhu'i interpretation method through the science of munasabah analysis, interpretation of verses with verses, hadiths and so on. Based on the results of this study, it can be concluded that the husband's obligation to his wife in a household to ensure survival (livelihood) is a matter that certainly exists in establishing a husband-wife relationship and must be fulfilled with full responsibility. Contemporary scholars state this problem in QS. An Nisa'(4): 34 at the point of giving maintenance can also be done by the wife, but in this day and age many husbands do not give their wives maintenance and only wives who earn a living in meeting household needs, this is due to the lack of religious knowledge and proper understanding among the people today.